2007
DOI: 10.1002/jcp.20971
|View full text |Cite
|
Sign up to set email alerts
|

Injury of skeletal muscle and specific cytokines induce the expression of gap junction channels in mouse dendritic cells

Abstract: Dendritic cells (DCs) in culture express at least connexin43, a protein subunit of gap junctions, and form gap junction channels, which could be important for T-cells activation. Here, we evaluated whether DCs express connexins in vivo and also to identify components of their microenvironment that regulate the functional expression of gap junctions. In vivo studies were performed in lymph nodes of mice under control conditions or after skeletal muscle damage. In double immunolabeling studies, connexin45 was fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 75 publications
3
39
0
Order By: Relevance
“…In the present study, we provide evidence supporting the notion that gap junctions are indeed formed between Ag-presenting DCs and T cells and these structures are required for efficient T cell activation by DCs. It was recently reported that TNF-␣ plus IL-1␤, as well as IFN-␥ induce transient gap junctional communication between monocytes/macrophages or primary DCs and DC-derived cell lines (10,12,13). In contrast, in the experiments reported here, no additional cytokine stimuli were required, in addition to the specific Ag, to observe dye coupling between DCs and T cells.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…In the present study, we provide evidence supporting the notion that gap junctions are indeed formed between Ag-presenting DCs and T cells and these structures are required for efficient T cell activation by DCs. It was recently reported that TNF-␣ plus IL-1␤, as well as IFN-␥ induce transient gap junctional communication between monocytes/macrophages or primary DCs and DC-derived cell lines (10,12,13). In contrast, in the experiments reported here, no additional cytokine stimuli were required, in addition to the specific Ag, to observe dye coupling between DCs and T cells.…”
Section: Discussionmentioning
confidence: 56%
“…Ly (5% weight to volume Ly dissolved in 150 mM LiCl) was microinjected into DCs through glass microelectrodes by brief overcompensation of the negative capacitance circuit in the amplifier until the impaled cell was brightly fluorescent. Gap junctional communication was tested by observing whether dye transfer occurred to T cells during the first minutes after dye injection, as described previously (13). The incidence of dye coupling was calculated by dividing the number of injected cells showing dye transfer to more than one neighboring cell by the total number of cells injected in each experiment multiplied by 100.…”
Section: Dye Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of GJ channels in immune cells has been associated with activation and coordination of specific events, such as transmigration, protease secretion, antigen presentation and cell differentiation (14,15,33,(35)(36)(37)(38). All these functions require cell specific activation that is driven by the indirect action of soluble inflammatory factors.…”
Section: Discussionmentioning
confidence: 99%